Transesterification of diethyl oxalate with phenol using MoO3/SiO2 catalyst - Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Applied Catalysis A-General, 2005)
Transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in liquid phase using MoO3/ SiO2 solid acid catalyst with high conversion and 100% selectivity. A series Of MoO3/SiO2 catalysts with different Mo loadings (1-20 wt%) were prepared using sol-gel technique and characterized using X-ray diffraction analysis (XRD), BET specific surface area, temperature-programmed desorption (TPD) of ammonia, and FTIR spectroscopic analysis of adsorbed pyridine. XRD analysis revealed the amorphous nature of the catalyst up to 10 wt% MoO3 loading and the formation of crystalline α-MoO3 phase on amorphous silica support with higher MoO3 loading. BET surface area showed high surface area for catalysts prepared by sol-gel technique with lower MoO3 content; the surface area decreases with increasing MoO3 loading. Ammonia TPD shows much higher acid strength compared to the catalysts prepared by impregnation technique. Among the series of catalysts prepared, MoO3/SiO2 containing 1 wt% MoO3 was found to be the most active catalyst for transesterification reaction, with a maximum DEO conversion of 80.9 and 100% selectivity for DPO. The effects of reaction temperature and catalyst concentration on conversion and product selectivity have been investigated. © 2005 Elsevier B.V. All rights reserved.
Keywords: diethyl oxalate; diphenyl oxalate; MoO3/SiO2; sol-gel technique; transesterification

Transesterification of diethyl oxalate with phenol over sol-gel MoO3/TiO2 catalysts - Kotbagi, Trupti; Duy Luan Nguyen; Lancelot, Christine; Lamonier, Carole; Thavornprasert, Kaew-Arpha; Zhu Wenli; Capron, Mickael; Jalowiecki-Duhamel, Louise; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck (Chemsuschem, 2012)
The transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in the liquid phase over very efficient MoO3/TiO2 solid-acid solgel catalysts. A selectivity of 100?% with a remarkable maximum yield of 88?% were obtained, which opens the route to downstream phosgene-free processes for the synthesis of polycarbonates. Interpretation of the results of various acidity measurements (NH3 and pyridine desorption, methanol oxidation as a probe reaction) allowed us to identify the catalytic sites as Lewis acid sites.
Keywords: heterogeneous catalysis; Lewis acids; Oxidation; sol-gel processes; transesterification

Template-free sol-gel synthesis of high surface area mesoporous silica based catalysts for esterification of di-carboxylic acids - More, Pavan M.; Umbarkar, Shubhangi B.; Dongare, Mohan K. (Comptes Rendus Chimie, 2016)
High surface area mesoporous silica based catalysts have been prepared by a simple hydrolysis/sol-gel process without using any organic template and hydrothermal treatment. A controlled hydrolysis of ethyl silicate-40, an industrial bulk chemical, as a silica precursor, resulted in the formation of very high surface area (719 m(2)/g) mesoporous (pore size 67 angstrom and pore volume 1.19 cc/g) silica. The formation of mesoporous silica has been correlated with the polymeric nature of the ethyl silicate-40 silica precursor which on hydrolysis and further condensation forms long chain silica species which hinders the formation of a close condensed structure thus creating larger pores resulting in the formation of high surface mesoporous silica. Ethyl silicate-40 was used further for preparing a solid acid catalyst by supporting molybdenum oxide nanoparticles on mesoporous silica by a simple hydrolysis sol gel synthesis procedure. The catalysts showed very high acidity as determined by NH3-TPD with the presence of Lewis as well as Brensted acidity. These catalysts showed very high catalytic activity for esterification: a typical acid catalyzed organic transformation of various mono- and di-carboxylic acids with a range of alcohols. The in situ formed silicomolybdic acid heteropoly-anion species during the catalytic reactions were found to be catalytically active species for these reactions. Ethyl silicate-40, an industrial bulk silica precursor, has shown a good potential for its use as a silica precursor for the preparation of mesoporous silica based heterogeneous catalysts on a larger scale at a lower cost. (C) 2016 Published by Elsevier Masson SAS on behalf of Academie des sciences.